Genistein Content and Tyrosinase Inhibitory Activity of Edamame (Glycine max) Extracts - Indah Yulia Ningsih; Lisa Kusuma Wardhani; Annisa Ragdha Eka Nuryuanda; Endah Puspitasari; Mochammad Amrun Hidayat (Journal of Tropical Pharmacy and Chemistry, 2022)
The study aimed to determine genistein content and tyrosinase inhibition activity of 70% ethanolic and ethyl acetate extracts of edamame (Glycine max) with an extraction time of 15, 30, and 60 minutes. Extraction was performed using the ultrasonication method. Determination of genistein content was carried out using TLC-densitometry. Furthermore, all samples were tested for their tyrosinase inhibition activity using the spectrophotometric assay. Ethyl acetate extract with 60 min of extraction time exhibited the highest extraction yield (6.414% w/w), the highest genistein content (0.169 ± 0.007% w/w), and the highest tyrosinase inhibition activity (IC50 = 72.420 ± 0.550 µg/mL). It was known that the genistein content of 70% ethanolic and ethyl acetate extracts affected tyrosinase inhibition activity with correlation coefficient (r) values of 0.9973 and 0.9826, respectively. G. max was suggested as a tyrosinase inhibitor agent from natural sources for skin whitening product development due to its isoflavones content, mainly genistein.